Vector-borne Rickettsia Pathogens - Yuexun Tian; Phillip E. Kaufman; Cynthia C. Lord (EDIS, 2024)
The genus Rickettsia contains species that are important in human health as they cause several serious diseases such as Rocky Mountain spotted fever. This publication summarizes the human-disease-causing pathogens in the genus Rickettsia in the United States and delivers general knowledge of their vectors and the diseases they cause. Prevention and management of disease-causing Rickettsia species, mainly for vector control agencies and entities, are also discussed. This publication is written for audiences of all ages and with any educational background and serves as a resource for public education.